RETAINING EMPLOYEE COMMITMENT: UNDERSTANDING FACTORS IN RETENTION MANAGEMENT AT THE MINISTRY OF INVESTMENT/BKPM A CASE STUDY IN THE NON-INDUSTRIAL LICENSING DIRECTORATE - Ilham Ramadhandi Alamsyah (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to determine the factors that influence employee retention and commitment within the Directorate of Non-Industrial Licensing at the Ministry of Investment/BKPM. The main goal is to understand how job satisfaction, organizational support, and career development influence employee retention. This research addresses the challenge of retaining a high-performing and committed workforce, which is critical to achieving the Ministry's strategic objectives. The Ministry of Investment/BKPM, since its transformation from BKPM, has made a significant contribution to increasing foreign and domestic investment through improving licensing and facilitation processes. This research was conducted through a qualitative approach using the triangulation method to obtain comprehensive employee insight. The internship program is focused on analyzing retention management practices, organizational support systems, and career development opportunities in the Ministry. Key accomplishments include detailed assessments of employee perceptions of job satisfaction, effectiveness of organizational policies, and clarity of promotion processes. Based on these findings, several recommendations are proposed to improve retention strategies. Continuous evaluation and improvement of organizational practices, policies and processes is essential. Factors such as a supportive work environment and fair treatment were identified as important factors for employee commitment, while ambiguity in the promotion process was an issue. Future internship programs should focus on analyzing these aspects more thoroughly and implementing regular feedback sessions to understand employee perspectives better. This will help in increasing employee commitment and satisfaction.